The role of social capital in enhancing economic resilience during the Covid-19 Pandemic in Bantul Regency - Dwi Riyanti; Ridho Harta (Jurnal Civics: Media Kajian Kewarganegaraan)
This study purposed to examine social capital in economic resilience in Bantul Regency during the pandemic. This study was case study where the data were obtained through interview, observation, and documentation. This study involved Legal Department of Bantul Regional Government, Trade Service, Association of Indonesian Market Traders (APPSI) at Imogiri Market, Semampir Market, Bantul Market, Angkruksari Market, Bantul Market Traders, Angkruksari Market Traders, Ngangkruk Market Traders, Semampir Market Traders, Alfamart Franchise Networked Modern Market Managers in Bantul Regency, Parangtritis Alfamart, and Non-networked Modern Markets Franchise Stores ‘Risky’ and ‘Lestari’. This study resulted that the Bantul Regency Government had taken a step in public policy in economic resilience with social capital approach. The success of this social capital-based public policy was seen from the public's acceptance against the policy, a relatively stable economic depth index between 2019-2020, and the involvement of APPSI social organization as a mediator and facilitator between the community and the government. The empowered social capital was the value of cooperation, social networks, and trust in the community. This study still had any limitation and needed to be expanded to produce comprehensive data with some future studies.